2023
DOI: 10.1038/s41598-023-41718-w
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of internal temperatures of commercially-available 18650 lithium-ion batteries

Casey M. Jones,
Meghana Sudarshan,
R. Edwin García
et al.

Abstract: Direct access to internal temperature readings in lithium-ion batteries provides the opportunity to infer physical information to study the effects of increased heating, degradation, and thermal runaway. In this context, a method to insert temperature sensors into commercial 18650 cells to determine the short- and long-term effects through characterization testing is developed. Results show that sensor insertion only causes a decrease in capacity of 0.5–2.3%, and an increase in DC resistance of approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…14,49 Heat could be another factor promoting the electrolyte decomposition as it was previously reported that the temperature was higher at the inner region than the outer region for the cylindrical cells. 31,[50][51][52] This issue could become more severe for larger size cylindrical cells, such as 46 800. As the battery transitioned from electrolyte-rich to electrolyte-lean, side reactions at the anode side, including Li-plating, transition-metal crossover and deposition, and accumulation of electrolytedecomposition byproducts, aggravated and exhibited significant spatial-heterogeneity.…”
Section: Vicious Cycles In Fast-charging Batteriesmentioning
confidence: 99%
“…14,49 Heat could be another factor promoting the electrolyte decomposition as it was previously reported that the temperature was higher at the inner region than the outer region for the cylindrical cells. 31,[50][51][52] This issue could become more severe for larger size cylindrical cells, such as 46 800. As the battery transitioned from electrolyte-rich to electrolyte-lean, side reactions at the anode side, including Li-plating, transition-metal crossover and deposition, and accumulation of electrolytedecomposition byproducts, aggravated and exhibited significant spatial-heterogeneity.…”
Section: Vicious Cycles In Fast-charging Batteriesmentioning
confidence: 99%